Teachers' Efforts in Forming the Religious Character of Students at Ketawanggede Elementary School, Malang City - Islam, Muhammad Thoriqul; Ahmad Wahyulil Albab; Amit Dana Ikmah; Dwiana Novitasari; Fatkhul Khabib (CV. Gerasi Insan Nusantara, 2025)
Education in Indonesia cannot be separated from Islamic values, which have become an integral part of the education system. Ketawanggede Elementary School, Malang City, is one example of a school that implements Islamic education through school culture as a means of instilling Islamic values ​​to shape the religious character of students. Instilling these values from an early age is important so that students not only excel academically but also can practice their religious values in their daily lives. This study aims to: (1) identify the Islamic values ​​instilled through school culture; (2) describe the process of religious character formation; and (3) identify the supporting and inhibiting factors in this process. This study uses a descriptive qualitative approach with data collection techniques in the form of interviews, observation, and documentation. Data analysis is carried out through reduction, presentation, and conclusion, as well as data validation using triangulation of sources and techniques. The results of the study indicate that the instilled Islamic values ​​include faith, sharia, and morals. The formation process is carried out through habituation, advice, and role models. The supporting and inhibiting factors include the role of students, educators, school facilities, and parental involvement.